Effect of dietary supplementation with different forms of chromium on feed intake, milk production and composition, blood parameters of Afshari ewes in transition period under the influence of heat stress - Asadi, M; Ghoorchi, T; Toghdory, AH (Journal of the Hellenic Veterinary Medical Society, 2025)
The study evaluated the effect of using different forms of chromium in Transition period on feed intake, milk production and composition, blood parameters of Afshari ewes and their newborn lambs under the influence of heat stress. Forty pregnant ewes were assigned to four experimental treatments with ten replications from 42 ± 2 days before the expected birth in a completely randomized design. Experimental treatments include basic diet without chromium supplement (control), basic diet containing 3 mg of chromium in mineral form per kg of dry matter, basic diet containing 3 mg of chromium in the form of chromium-methionine per kg of dry matter and diet The base contained 3 mg of chromium in the form of chromium nanoparticles per kilogram of dry matter. The experiment started 42 days before calving and lasted for 84 days. The results showed that there was no significant difference in the weight of the ewes before lambing. But from the beginning of ewes giving birth to 6 weeks after giving birth, the treatments receiving different forms of chromium performed better than the control group of ewes. Dry matter consumption of ewes also had an upward trend from the third to the sixth week after giving birth in the ewes receiving chromium-methionine and chromium nanoparticles (P < 0.05). Adding chromium to the diet of ewes under heat stress increases daily milk production and chromium concentration in milk (P˂0.05).blood malondialdehyde, cortisol concentrations, glucose, urea and cholesterol in the treatments receiving different forms of chromium also decreased compared to the control group (P<0.05). Also, by adding chromium supplement to the diet, the concentration of superoxide dismutase also increased (P<0.05). In general, it is recommended to receive chromium, especially in the form of chromium-methionine and chromium nanoparticles, during the transition period of ewes under the influence of heat stress.